Contabilidade de custos no setor público: fatores contingenciais que afetam sua implantação nas universidades federais brasileiras - Nottar, Daiane Inacio da Silva (2022)
This research aimed to identify the contingency factors that affect the implementation of cost accounting in Brazilian federal universities and to understand how these factors influence its adoption. Therefore, a descriptive and explanatory study was carried out, with a quantitative and qualitative approach. Data collection took place between 09/15 and 11/15/2021 through the application of a survey questionnaire and semi-structured interviews with accountants and managers in the finance and budget area of Brazilian federal universities. 56 responses were obtained from the structured questionnaire sent to 69 universities and 7 semi-structured interviews were carried out in 7 universities in different locations. The analysis was performed based on descriptive statistics and Bardin's thematic analysis. The results indicate that most universities are in the initial stage of implementing a cost system, although such a system is perceived by the participants as important for Public Administration. Regarding the environmental contingency factor, it was found that the legislation contributes positively, since the public service has a strong legislative link, however, inspection/control bodies and society did not prove to be influential, as there is no effective charge on cost information. The structure factor showed an inflexible scenario, which makes it difficult to create new sectors, and there is also a need for personnel who can dedicate themselves to working on the subject in the institutions. As for the strategy factor, due to the low demand of managers for managerial information, the implementation of a cost system turns out not to be a priority, consequently, few universities are at advanced levels of implementation. The technology factor proved to be essential to the implementation, since the existence of a technical team, adequate hardware and software, as well as structuring systems, support and facilitate the process. As for the size factor, the complexity of the activities proved to be an obstacle, as the activities developed are diversified, and make it difficult to separate costs, and, in relation to the number of staff and students, it did not prove to be an influence, because, in the perception of the participants, the implementation of a cost system does not depend on the size of the institution. Finally, the organizational culture factor showed that the lack of a culture of cost calculation and resistance to changes hamper the implementation, as there is often a lack of visualization of the real usefulness that cost information will provide. Thus, it is concluded that, in the participants' perception, contingency factors, such as inflexibility of the organizational structure, need forpersonnel, absence of software and specialized technical team available, complexity of activities, lack of a cost culture and resistance to change, are factors that make it difficult to implement a cost system. On the other hand, legislation, media, technical knowledge, training and structuring systems proved to be contributory. It was also observed that the low communication between universities and the lack of methodological standardization regarding the calculation of costs ends up being harmful to the development of the theme, and that cultural changes are fundamental to contribute to this evolution. The research allowed us to identify impacting factors in the implementation of a cost system, which contributes to the advancement of the subject in the public area.